Genome-wide identification and analysis of wheat LRR-RLK family genes following Chinese wheat mosaic virus infection - Liu, Shuang; Lei, Jiajia; Zhang, Juan; Liu, Hanhong; Ye, Zhuangxin; Yang, Jin; Lu, Qiseng; Liu, Peng; Chen, Jianping; Yang, Jian (Frontiers in Plant Science, 2023)
As the largest plant receptor-like protein kinase (RLK) superfamily, the leucine-rich repeat receptor-like kinases (LRR-RLKs) family are involved in plant growth, development, and stress responses. However, the functions of LRR-RLKs in wheat immunity remain unknown. In the current study, 929 LRR-RLKs were identified in Triticum aestivum genome database and divided into 14 clades. Chromosomal localization and synteny analysis revealed that TaLRR-RLKs were randomly distributed on all chromosomes with 921 collinear events. Through the cis-acting elements analysis, we observed that TaLRR-RLKs participated in hormone response, light response, development, metabolism, and response to environmental stress. The transcript level of 14 random selected TaLRR-RLKs from each subfamily was regulated by plant hormone treatment and Chinese wheat mosaic virus (CWMV) infection. The function of TaLRR-RLKs in wheat resistance to CWMV infection was further investigated by virus-induced gene silencing assay. Additionally, the accumulation of MeJA response genes, as well as CWMV RNA were not changed in the TaLRR-RLK silencing plants under MeJA treatment. Our results demonstrated that TaLRR-RLKs play an important role in wheat resistance to viral infection via hormone signals and lay the groundwork for the functional study of TaLRR-RLKs in wheat.